Hypoxia Created Human Mesenchymal Stem Cell Sheet for Prevascularized 3D Tissue Construction. Issue 3 (14th December 2015) - Zhang, Lijun; Xing, Qi; Qian, Zichen; Tahtinen, Mitchell; Zhang, Zhaoqiang; Shearier, Emily; Qi, Shaohai; Zhao, Feng
Abstract : 3D tissue based on human mesenchymal stem cell (hMSC) sheets offers many interesting opportunities for regenerating multiple types of connective tissues. Prevascularizing hMSC sheets with endothelial cells (ECs) will improve 3D tissue performance by supporting cell survival and accelerating integration with host tissue. It is hypothesized that hypoxia cultured hMSC sheets can promote microvessel network formation and preserve stemness of hMSCs. This study investigates the vascularization of hMSC sheets under different oxygen tensions. It is found that the HN condition, in which hMSC sheets formed under physiological hypoxia (2% O2 ) and then cocultured with ECs under normoxia (20% O2 ), enables longer and more branched microvessel network formation. The observation is corroborated by higher levels of angiogenic factors in coculture medium. Additionally, the hypoxic hMSC sheet is more uniform and less defective, which facilitates fabrication of 3D prevascularized tissue construct by layering the prevascularized hMSC sheets and maturing in rotating wall vessel bioreactor. The hMSCs in the 3D construct still maintain multilineage differentiation ability, which indicates the possible application of the 3D construct for various connective tissues regeneration. These results demonstrate that hypoxia created hMSC sheets benefit the microvessel growth and it is feasible to construct 3D prevascularized tissue construct using the prevascularized hMSC sheets. Abstract : Vascularization of human mesenchymal stem cell (hMSC) sheet is significantly enhanced by growing hMSCs under physiological hypoxia (2% O2 ) and then coculturing endothelial cells under normoxia (20% O2 ), which is consistent with the presence of high levels of angiogenic factors in the coculture microenvironment. A 3D hMSC tissue with interconnected microvessel network is successfully engineered using the prevascularized hMSC cell sheets.